Reliability of three-dimensional motion analysis during single-leg side drop landing test after anterior cruciate ligament reconstruction: An in vivo motion analysis study - Johnson Chun Yiu Pang; Rachel Suet Wai Tsang (World Scientific Publishing, 2022)
Background: Anterior cruciate ligament (ACL) injury is a common sport injury and investigation of landing biomechanics is helpful in injury prevention and rehabilitation. Recent study found a lateral single-leg drop landing test resulted in the highest peak knee valgus angle (PKVA), but its reliability on patients who received ACL reconstruction (ACLR) is unknown. Objective: This study aimed to investigate the reliability in both within and between days on the normalized vertical ground reaction force (NVGRF) and kinematics of lower limbs after receiving ACLR. The findings can form the cornerstone for further study related to lateral jumping-and-landing biomechanics in patients with ACLR. Methods: This was a test-retest reliability study. Twelve patients (four females and eight males) who received ACLR with mean age of 29.4 (SD [Formula: see text] 1.66) were recruited. The subjects were instructed to jump laterally from 30[Formula: see text]cm height and landed with single-leg for five times. The procedure was conducted on both legs for comparison. The NVGRF and local maxima of the hip, knee and ankle angles during the first 100[Formula: see text]ms in all three planes were analyzed. The measurement was conducted by the same assessor to evaluate the within-session reliability, and the whole procedure was repeated one week later for the evaluation of the between-session reliability. Intra-class correlation coefficient (ICC) test was used to assess the within- and between-session reliability by ICC (3, 1) and ICC (3, K) respectively. Results: The within-session reliability of NVGRF [ICC (3, 1)] was 0.899-0.936, and its between-session reliability [ICC (3, K)] was 0.947-0.923. Overall reliability for kinematics within-session [ICC (3, 1)] was 0.948-0.988, and the between-session reliability [ICC (3, K)] was 0.618-0.982, respectively. Good to excellent reliability for the lateral single-leg drop landing test was observed in most of the outcome measures for within- and between-session. The ICC value of NVGRF of ACLR leg was lower than that of the good leg in the within-session which may associate with lower neuromuscular control in ACLR leg than that of the good leg. Conclusion: The results of this study support the use of a lateral single-leg drop landing test to evaluate lower limb biomechanics for ACLR.